Indicators of aging in people with disabilities. The perception of families (European Journal of Child Development, Education and Psychopathology, 2019)
The article presents the results of a research on the perception that the relatives of elderly people with intellectual disabilities have in relation to the aging process and, particularly, of the most significant or relevant signs that they begin to detect in their relatives in areas such as cognitive, emotional, social or work and about their worries about the future. The quantitative method has been used, specifically type survey through the design of an instrument of own elaboration and subjected to a process of validation by experts. Regarding the results obtained, the areas of greatest concern are those related to emotional and social aspects, where the signs or symptoms perceived by family members in their sons and daughters have obtained higher scores, especially those related to the increase in concerns such as loss of family and friends, fear of the appearance of illnesses, death itself, followed by changes in coexistence in the future. Likewise, those referred to the economic or material well-being and to be able to have a center that maximizes their autonomy, are priority for families.